Study of bacterial diversity in the oral cavity of Malaysian subjects / Teoh Wuen Yew - Teoh, Wuen Yew (2010)
About 700 species of bacteria can inhabit the human oral cavity. This project initially investigated the bacterial diversity within the oral cavity of Malaysian subjects by using culture-dependent techniques and 16S rDNA sequence analysis. The second part of the research profiled the antibiotic resistance of the identified oral bacteria by the Etest method. Three sampling sites of the oral cavity from nine healthy subjects were analyzed: the tooth surface, gingival crevice, and dorsum of the tongue. The tooth surface was shown to harbor 41 species, gingival crevice harbored 51 species and tongue dorsum 41 species. On average, each subject carried 27 species from all the three sites. Streptococcus mutans, a putative cariogenic pathogen and Prevotella intermedia, a putative periodontal pathogen were detected. In this study, no novel species of oral bacteria were identified. The bacteria that inhabit in the oral cavity are a diverse and dynamic community. Some bacterial species showed a pattern of site-specificity and subject-specificity while some are common in all sites of the oral cavity and in all subjects. All 411 isolates were susceptible to amoxicillin-clavulanic acid except Pseudomonas aeruginosa which showed high resistance (MIC >256μg/ml). 24 of the 411 isolates (5.8%) were resistant to clindamycin. The resistant strains included Capnocytophaga gingivalis, Eikenella corrodens, Haemophilus parainfluenzae, Lautropia sp., Neisseria sp., N. meningitidis, N. flavescens, N. subflava, Streptococcus sanguinis, S. mitis and P. aeruginosa.